Adherence to Iron Chelation Therapy and Its Determinants - Sidhu, Sukhmani (Int J Hematol Oncol Stem Cell Res, 2021)
Background: Thalassemia is a chronic disease requiring lifelong treatment. The adherence to regular iron chelation therapy is important to ensure complication-free survival and good quality of life. The study aim to assess the adherence to iron chelation therapy (ICT) in patients with transfusion-dependent thalassemia (TDT), evaluate various causes of non-adherence and study the impact of non-adherence on the prevalence of complications secondary to iron overload. Materials and Methods: Patients with TDT on ICT for > 6 months were enrolled in the study. Hospital records were reviewed for demographic details, iron overload status, treatment details, and the prevalence of complications. A study questionnaire was used to collect information on adherence to ICT, knowledge of patients, and the possible reasons for non-adherence.   Results:  A total of 215 patients with a mean age of 15.07+7.68 years and an M: F ratio of 2.2:1 were included in the study. Non-adherence to ICT was found in 10.7% of patients. Serum ferritin levels were significantly higher in the non-adherent group (3129.8+1573.2 µg/l) than the adherent population (2013.1+1277.1 µg/l). Cardiac as well as severe liver iron overload was higher in the non-adherent patients. No correlation was found between disease knowledge and adherence to ICT. Difficulties in drug administration and many medicines to be taken daily were statistically significant reasons for non-adherence. There was no difference in the co-morbidities arising due to the iron overload in the two groups. Conclusion: Nearly 11% of patients with TDT were non-adherent to ICT. Non-adherence results in higher iron overload.